(untitled) (Research, Society and Development, 2021)
Most post-COVID-19 patients need physical therapy rehabilitation during and shortly after hospitalization according to the World Health Organization. And the physical therapy rehabilitation program has an emphasis and greater importance on the cardiorespiratory system. The aim of this article is to demonstrate how physical therapy resources can help improve these Post-Covid 19 patients, regardless of their status, whether mild, moderate or severe, based on research carried out on digital platforms: Scielo, Pubmed, Associações International with the descriptors coronavirus, pathophysiology and treatment, during a period of 6 months. Based on the researches carried out, it can be concluded that physical therapy rehabilitation through resources such as: thresold (linear pressure load device), RPPI (intermittent positive pressure breathing), manual resuscitator and resistance exercises can improve cardiorespiratory capacity and promote greater tolerance to the reconditioning of Post-Covid 19 patients, consequently improving their quality of life.